CDADC1 is a vertebrate-specific dCTP deaminase that metabolizes gemcitabine and decitabine to prevent cellular toxicity - Marcelo M. Rodriguez; Debashree Chatterjee; Johanna Guerry; Anne-Marie Patenaude; Charles C. H. Cohen; Therence Bois; Ariane Larouche; Silvana R. Ferreira; Thierry Bertomeu; Andrew Chatr-aryamontri; Li Zhang; Sylvie Mader; et al. (Proceedings of the National Academy of Sciences, 2025)
Cancer therapy is limited by resistance to standard-of-care chemotherapeutic and/or by treatment-associated toxicity. Identifying molecular mechanisms that modulate cellular toxicity is crucial for enhancing treatment efficacy. We characterize CDADC1, a vertebrate-specific orphan enzyme, as an unprecedented eukaryotic dCTP deaminase. CDADC1 catalyzes the conversion of dCTP into dUTP. While bacteria use this activity to sustain proliferation, CDADC1 evolved independently and is not required for mammalian cell proliferation, as demonstrated in cell lines and by the normal growth and standard lifespan of Cdadc1-deficient mice. However, we uncover a role of CDADC1 in metabolizing nucleotide analogs gemcitabine and decitabine. Gain- and loss-of-function assays in cancer cell lines, along with ectopic mouse models of pancreatic cancer, show that CDADC1 reduces these drugs’ efficacy. By the same token, Cdadc1 −/− mice are hypersensitive to gemcitabine. Mechanistically, CDADC1 deaminates the active triphosphate form of gemcitabine and decitabine, rendering them susceptible to inactivation by deoxyuridine triphosphatase. In contrast, the dCMP deaminase DCTD contributes to cell proliferation and promotes gemcitabine and decitabine toxicity. Thus, CDADC1 underpins a previously unrecognized mechanism of intrinsic chemoresistance in cancer cells and has a nonredundant role in protecting from gemcitabine toxicity. CDADC1 reveals a clinically relevant metabolic pathway that might be exploited to enhance the efficacy of deoxycytidine analogs but calls for assessing CDADC1 status to avoid lethal toxicities.